2022
DOI: 10.1186/s12893-022-01715-8
|View full text |Cite
|
Sign up to set email alerts
|

Does temporary ileostomy via specimen extraction site affect the short outcomes and complications after laparoscopic low anterior resection in rectal cancer patients? A propensity score matching analysis

Abstract: Purpose The purpose of the current study was to compare the outcomes of temporary stoma through the specimen extraction site (SSES) and stoma through a new site (SNS) after laparoscopic low anterior resection. Methods The rectal cancer patients who underwent laparoscopic low anterior resection plus temporary ileostomy were recruited in a single clinical database from Jun 2013 to Jun 2020. The SSES group and the SNS group were compared using propens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Four studies were completed in China ( 19 , 21 , 25 , 27 ), two studies ( 18 , 20 ) in Korea and one study ( 26 ) in Turkey. Three studies ( 21 , 25 , 26 ) performed prophylactic ileostomy at the right lower abdominal SES, two studies ( 18 , 19 ) performed ileostomy at the left lower abdominal SES, one study ( 27 ) performed ileostomy at the median lower abdominal SES, and one study ( 20 ) performed ileostomy at either the left lower abdominal or right lower abdominal SES. All included studies were retrospective in design ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies were completed in China ( 19 , 21 , 25 , 27 ), two studies ( 18 , 20 ) in Korea and one study ( 26 ) in Turkey. Three studies ( 21 , 25 , 26 ) performed prophylactic ileostomy at the right lower abdominal SES, two studies ( 18 , 19 ) performed ileostomy at the left lower abdominal SES, one study ( 27 ) performed ileostomy at the median lower abdominal SES, and one study ( 20 ) performed ileostomy at either the left lower abdominal or right lower abdominal SES. All included studies were retrospective in design ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies ( 19 21 , 25 – 27 ) reported operation time. The time of operation in the prophylactic ileostomy via the SES was shorter than that in the prophylactic ileostomy via NS after LRCS (MD = -0.43, 95% CI: -0.54 - -0.32 min; p<0.00001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations